Analisis Manajemen Kesiswaan Dalam Mengatasi Fluktuasi Jumlah Peserta Didik Di Sekolah Dasar - Historika Ditawati (ALACRITY : Journal of Education, 2026)
This study aims to analyze student management in overcoming fluctuations in the number of students at SD Negeri Lawu 02 Nguter Sukoharjo. The research uses a qualitative descriptive approach with a case study method. Data was obtained through documentation of the number of new students over the past five years, then analyzed descriptively to identify fluctuation patterns and factors that affect them. The results of the study show that the number of students in the school has fluctuated from year to year. This condition is influenced by internal factors in the form of lack of innovation in learning programs and strategies, external factors in the form of competition between schools, and public trust factors related to the image and quality of educational services. These fluctuations not only reflect quantitative changes, but also show problems in the management of student management and the attractiveness of schools in the eyes of the public. To overcome these problems, it is necessary to implement integrated education management functions which include planning, organizing, implementing, supervising, and evaluating. The proposed strategies include strengthening digital-based school branding, implementing trial class programs, developing superior programs, strengthening partnerships with PAUD/TK, and data-based decision-making. Thus, the implementation of innovative and adaptive student management is expected to increase the number of students and strengthen public trust in schools in a sustainable manner.